2016
DOI: 10.1111/dom.12650
|View full text |Cite
|
Sign up to set email alerts
|

Differences in homeostatic model assessment (HOMA) values and insulin levels after vitamin D supplementation in healthy men: a double‐blind randomized controlled trial

Abstract: Vitamin D is thought to play a role in glucose metabolism. The aim of the present study was to determine the effect of vitamin D supplementation on markers of insulin sensitivity and inflammation in men without diabetes with vitamin D deficiency/insufficiency. In this 1-year double-blind randomized controlled trial, 130 men aged 20-65 years (mean age 47.52 ± 11.84 years) with serum 25-hydroxyvitamin D levels <50 nmol/l (mean 38.89 ± 8.64 nmol/l) were randomized to treatment (100 000 IU vitamin D bimonthly) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…The search yielded 1280 citations after removal of duplicates. We screened the full text of 242 papers, and identified 14 relevant trials ( Shahgheibi et al, 2016 ; Vaziri et al, 2016 ; Saad et al, 2018 ; Talaat et al, 2016 ; Taheri et al, 2015 ; Tepper et al, 2016 ; Zarrin et al, 2017 ; Kamelian et al, 2017 ; Jozanikohan and Kazemi Saleh, 2015 ; Mohammad-Alizadeh-Charandabi et al, 2015 ; Shehata, 2016 ; Rahme et al, 2017 ; Mojibian et al, 2015 ; Behjat Sasan et al, 2017 ).…”
Section: Randomized Trials Of Vitamin D Supplementation In Different mentioning
confidence: 99%
See 1 more Smart Citation
“…The search yielded 1280 citations after removal of duplicates. We screened the full text of 242 papers, and identified 14 relevant trials ( Shahgheibi et al, 2016 ; Vaziri et al, 2016 ; Saad et al, 2018 ; Talaat et al, 2016 ; Taheri et al, 2015 ; Tepper et al, 2016 ; Zarrin et al, 2017 ; Kamelian et al, 2017 ; Jozanikohan and Kazemi Saleh, 2015 ; Mohammad-Alizadeh-Charandabi et al, 2015 ; Shehata, 2016 ; Rahme et al, 2017 ; Mojibian et al, 2015 ; Behjat Sasan et al, 2017 ).…”
Section: Randomized Trials Of Vitamin D Supplementation In Different mentioning
confidence: 99%
“…The current update identified 8 trials: 5 from Iran ( Taheri et al, 2015 ; Zarrin et al, 2017 ; Kamelian et al, 2017 ; Jozanikohan and Kazemi Saleh, 2015 ; Mohammad-Alizadeh-Charandabi et al, 2015 ), 1 from Egypt ( Shehata, 2016 ), one from occupied Palestine/Israel ( Tepper et al, 2016 ), and one from Lebanon ( El-Hajj Fuleihan et al, 2016 ; Rahme et al, 2017 ). The latter was included in our previous review ( Chakhtoura et al, 2017a ), since we had access to primary data, but it was not published then, and is described herein ( Table 1 ) ( El-Hajj Fuleihan et al, 2016 ; Taheri et al, 2015 ; Tepper et al, 2016 ; Zarrin et al, 2017 ; Kamelian et al, 2017 ).…”
Section: Randomized Trials Of Vitamin D Supplementation In Different mentioning
confidence: 99%
“…Most observational studies have confirmed that vitamin D status is inversely correlated with the BMI [7]. However, several randomized controlled trials (RCTs) and a recent meta-analysis on the effects of vitamin D supplementation on BMI did not seem to support this correlation [17][18][19][20]. On the other hand, several studies have suggested that central obesity is considered as a better predictor of several adverse health outcomes and mortality [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, low vitamin D status is associated with high levels of inflammatory factors such as IL-6, TNF-a, and C-reactive protein (28)(29)(30). Remarkably, recent clinical trials have indicated that supplementation of vitamin D may reduce the risk of diabetes mellitus by attenuating the development of insulin resistance rather than by lowering insulin secretion, supporting the association of vitamin D with insulin resistance in the pathogenesis of T2DM (31).…”
Section: Discussionmentioning
confidence: 87%